Exploring patients’ understanding of behavioral risk factors for non-communicable diseases: a study on diabetes and hypertension in Bushbuckridge, South Africa - Thabo D. Pilusa; Cairo B. Ntimana; Mahlodi P. Maphakela; Eric Maimela (BMC Public Health)
Abstract Background Non-communicable diseases (NCDs) account for 41 million annual deaths worldwide, or 74% of all deaths. Notably, 86% of the 17 million premature deaths attributed to NCDs occur in low- and middle-income countries. Despite the burden of these diseases, many patients lack sufficient knowledge of behavioral risk factors that contribute to NCDs. The study aimed to explore the knowledge of patients diagnosed with diabetes and hypertension about behavioral risk factors contributing to non-communicable diseases. Method The study employed a qualitative, explorative, and descriptive design. Data was collected through semi-structured interviews, and participants were selected purposively. The data analysis followed Tesch’s open thematic approach, applied at various levels and based on patient-provided text data, with the thematic analysis, the researcher was able to organize and interpret the data presented in the themes systematically. Results Four major themes emerged regarding the understanding of behavioral risk factors for non-communicable diseases among patients diagnosed with diabetes and hypertension. These include unhealthy eating habits and poor lifestyle choices, mental health issues and stress, challenges patients face in adhering to medications, and optimal management of their conditions, cultural practices, and beliefs. Conclusion The study shed some insights into the knowledge of patients diagnosed with diabetes and hypertension about behavioral risk factors contributing to NCD. They indicated that witchcraft, cultural beliefs, and inadequate health education could have resulted in NCDs, which influenced them to consult traditional healers before coming to the health facility. The observations of participants underscore the urgent need for targeted interventions to improve the knowledge of patients regarding behavioral risk factors for NCDs.